2018
DOI: 10.1002/jrs.5353
|View full text |Cite
|
Sign up to set email alerts
|

Laser crystallization of germanium nanowires fabricated by electrochemical deposition

Abstract: Germanium (Ge) nanowires were fabricated by electrochemical deposition on titanium‐coated silicon substrate. Arrays of nanowires with different mean diameters were obtained using indium nanoparticles of various sizes as centers of nucleation. Raman spectroscopy was used to establish the structural properties of nanowires under different laser excitation intensities. Cycles of measurements with different intensities demonstrated irreversible changes in the structure. Initial study with minimal excitation intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Analyzing the shape of spectra, presented in Figure , we note, that in both cases ( λ exc = 532 nm and λ exc = 633 nm), the spectra obtained with maximum excitation power and attenuated by two times do not change their shape and peak position. This fact is a normal thing for the majority of cases in Raman studies of bulk materials, but as it was demonstrated earlier, GeNWs obtained by ec‐LLS method may easily change their spectrum shape under low excitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analyzing the shape of spectra, presented in Figure , we note, that in both cases ( λ exc = 532 nm and λ exc = 633 nm), the spectra obtained with maximum excitation power and attenuated by two times do not change their shape and peak position. This fact is a normal thing for the majority of cases in Raman studies of bulk materials, but as it was demonstrated earlier, GeNWs obtained by ec‐LLS method may easily change their spectrum shape under low excitation.…”
Section: Resultsmentioning
confidence: 99%
“…Our further measurements of Samples 2 and 3 confirmed the results demonstrated earlier . For more convenience, in Figure , we presented only the Stokes component that was registered with 532 nm excitation wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gavrilov et al reported laser crystallization of germanium nanowires fabricated by electrochemical deposition. Detailed analysis of spectra shapes for samples with different mean diameters of Ge nanowires after exposure to high intensity laser radiation allows an estimation of the fraction of the crystalline phase in Ge nanowires . Grasseschi and co‐workers investigated the dynamics of dithiooxamide coordinated to gold NPs using SERS.…”
Section: Nanomaterialsmentioning
confidence: 99%